6c-3+5(c-4)+2=4c+7(c-3)

Simple and best practice solution for 6c-3+5(c-4)+2=4c+7(c-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6c-3+5(c-4)+2=4c+7(c-3) equation:


Simplifying
6c + -3 + 5(c + -4) + 2 = 4c + 7(c + -3)

Reorder the terms:
6c + -3 + 5(-4 + c) + 2 = 4c + 7(c + -3)
6c + -3 + (-4 * 5 + c * 5) + 2 = 4c + 7(c + -3)
6c + -3 + (-20 + 5c) + 2 = 4c + 7(c + -3)

Reorder the terms:
-3 + -20 + 2 + 6c + 5c = 4c + 7(c + -3)

Combine like terms: -3 + -20 = -23
-23 + 2 + 6c + 5c = 4c + 7(c + -3)

Combine like terms: -23 + 2 = -21
-21 + 6c + 5c = 4c + 7(c + -3)

Combine like terms: 6c + 5c = 11c
-21 + 11c = 4c + 7(c + -3)

Reorder the terms:
-21 + 11c = 4c + 7(-3 + c)
-21 + 11c = 4c + (-3 * 7 + c * 7)
-21 + 11c = 4c + (-21 + 7c)

Reorder the terms:
-21 + 11c = -21 + 4c + 7c

Combine like terms: 4c + 7c = 11c
-21 + 11c = -21 + 11c

Add '21' to each side of the equation.
-21 + 21 + 11c = -21 + 21 + 11c

Combine like terms: -21 + 21 = 0
0 + 11c = -21 + 21 + 11c
11c = -21 + 21 + 11c

Combine like terms: -21 + 21 = 0
11c = 0 + 11c
11c = 11c

Add '-11c' to each side of the equation.
11c + -11c = 11c + -11c

Combine like terms: 11c + -11c = 0
0 = 11c + -11c

Combine like terms: 11c + -11c = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4x-3-3x-2-x=10 | | 7x+30y=-7 | | (7+x)*(4+x)=100 | | (7x+1)(7x-1)-49(x+1)=4-98x | | x^2+6x^3+2x^2=0 | | x^2-1/3-x | | x^2-1/3-c | | 12+4x+3+7x= | | 4m-(m+3)=5m+2(-m+10) | | a^(-5)/a^7 | | a^(-5)/a67 | | T-2=19 | | -6=(3/4)h | | a^5/a^7 | | -6=3/4h | | 3x^2-12x-16/x-2 | | x+x(2x+1)=31 | | 4-(abs(2x))=3 | | 2=1.06 | | 6h^2+8h-9=0 | | 2x+8x-(6x+9)= | | 18-(2y+14)= | | 4/3y=1/8 | | Y-9=-1(x+6) | | -x-3/4-5-x/3 | | [-18+(-9)]+7= | | [-20+(-7)]+4= | | 4x^5-4x^4=0 | | f/8-21=-24 | | 12x=9(x+6) | | y+5y=28 | | 6cos^2x-1-cosx+1=0 |

Equations solver categories